Transitional cell carcinoma arising in a calyceal cyst mimicking a cystic renal tumour - Kim, Jeong Ho; Song, Joo Yeon; Lee, Wan (Canadian Urological Association Journal, 2014)
Solitary renal cysts are relatively common. The occurrence of transitional cell carcinoma (TCC) in a renal cyst is rare. We present the case of a 59-year-old man with a medical history of viral hepatitis B. During a workup for his hepatitis, a computed tomography scan revealed a large cystic tumour in the upper region of the left kidney. A radical left nephrectomy was performed. Microscopic examination of the cystic tumour revealed a grade 2 TCC. The cyst was lined by transitional epithelium. This is a case of a TCC growing within a renal calyceal cyst.